Impact of HSCT conditioning and glucocorticoid dose on exercise adherence and response - Wiskemann, Joachim; Kühl, Rea; Schmidt, Martina; Steindorf, Karen; Dreger, Peter; Bohus, Martin (Medicine and science in sports and exercise, 2017)
Purpose: Evidence from randomized controlled trials (RCT) that exercise interventions have beneficial effects in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) is growing. However, intensive chemotherapy conditioning and glucocorticoid (GC) treatment is always part of an allo-HSCT and possibly affect exercise adherence and training response. Therefore, we aimed to examine whether various conditioning protocols or different doses of GC treatment affect exercise adherence and/or training response during the inpatient period. Methods: We analyzed inpatient data from intervention groups of two large RCT in allo-HSCT patients (n = 113). The intervention incorporated partly supervised endurance and resistance exercise three to five times per week. According to the potentially interfering factors, the patients were divided into groups depending on intensity of conditioning (myeloablative conditioning (MAC), reduced-intensity conditioning (RIC), and nonmyeloablative conditioning (NMC)) and cumulative dose of GC treatment (GC low ≤9 mg·kg−1 prednisone or GC high >9 mg·kg−1 prednisone) and were compared. Results: Median exercise adherence (target value, five sessions weekly) during the inpatient period was 64% in MAC, 54% in RIC, and 63% in NMC. The proportion of prematurely terminated training sessions ranged from 11% to 15%. Tiredness was the most frequent cause of exercise termination in all groups. Exercise adherence, duration (min·wk1) and type of training was significantly associated with GC dose. With regard to training response, results suggest that GC-low patients tend to respond better in knee extensor muscle strength. Conclusions: Exercise adherence during inpatient period is significantly affected by dose of GC treatment but not by condition regimen. However, given the reasonable adherence rates also in the GC-high group, data support the feasibility and importance of exercising for all allo-HSCT patients during the inpatient period.